OTOMATISASI ACL SQUID PROXY SERVER BERBASIS WEB - Ragil Prihantoro, Candra (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2013)
Squid is the most widely used program by the network administrator as a program for squid proxy server is open source ( free ) that can be modified according to our wishes. In use squid proxy server must be configured directly to its squid file is to create a functioning ACL ( Access Control List ) manually . By writing scripts ACL ACL settings manually create quite prone to errors in setting and writing , it is because the complexity of the placement and write ACL scripts . If the administrator does not have the skills in the proxy server settings are still manually or still typing some script ACL , there will be difficulties in squid proxy server settings . Based on this background, the need for automation in the ACL Squid proxy -based web server that serves to facilitate configure squid proxy server in order to provide convenience and minimize errors on the write command squid proxy server ACL. The method used for the design automation Acl Squid Proxy Server Based Web consists of several stages: planning , data collection , analysis , design , system design , application development and preparation of reports.The results of this study in the form of web-based applications that can be used by the client to perform ACL configuration on squid proxy server so that the configuration changes made by administrators using the web based applications that have been made . Key words : Squid Proxy Server , Access Control List Squid , Otomatisasi Web based ACL